2018
DOI: 10.1371/journal.pntd.0006290
|View full text |Cite
|
Sign up to set email alerts
|

First cases of European bat lyssavirus type 1 in Iberian serotine bats: Implications for the molecular epidemiology of bat rabies in Europe

Abstract: Previous studies have shown that EBLV-1 strains exclusively hosted by Eptesicus isabellinus bats in the Iberian Peninsula cluster in a specific monophyletic group that is related to the EBLV-1b lineage found in the rest of Europe. More recently, enhanced passive surveillance has allowed the detection of the first EBLV-1 strains associated to Eptesicus serotinus south of the Pyrenees. The aim of this study is the reconstruction of the EBLV-1 phylogeny and phylodynamics in the Iberian Peninsula in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Eptesicus serotinus and E. isabellinus host distinct and characteristic EBLV‐1 virus strains, each with a different phylogenetic history (Vázquez‐Morón et al, ). A recent study has reported the first detection of an EBLV‐1 of the strain considered typical of E. isabellinus in an E. serotinus bat from northeastern Spain (Mingo‐Casas et al, ). The sequence of this virus is close to a known southern sequence of the virus, which suggests a recent transmission from E. isabellinus to E. serotinus, in agreement with the direction of the asymmetrical hybridization described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Eptesicus serotinus and E. isabellinus host distinct and characteristic EBLV‐1 virus strains, each with a different phylogenetic history (Vázquez‐Morón et al, ). A recent study has reported the first detection of an EBLV‐1 of the strain considered typical of E. isabellinus in an E. serotinus bat from northeastern Spain (Mingo‐Casas et al, ). The sequence of this virus is close to a known southern sequence of the virus, which suggests a recent transmission from E. isabellinus to E. serotinus, in agreement with the direction of the asymmetrical hybridization described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the other two lyssaviruses, WCBV and LLEBV, are linked to bats of the family Miniopteridae ( 30 ). Of these, only EBLV-1 and EBLV-2 have been reported to have caused rabies in humans, and more than 90% of the bat rabies cases have been associated with the bat species Eptesicus serotinus ( E. serotinus ) infected by EBLV-1 ( 12 ). The last European Union One Health 2018 Zoonoses Report confirmed bats as a reservoir for rabies in Europe, as it was present in 2% of the bats sampled ( 31 ).…”
Section: Historical Overview Of Rabies In Europementioning
confidence: 99%
“…During 1998–2003, a study of EBLV-1 viruses from E. isabellinus in southern Spain revealed the close communities in which EBLV-1 independently circulates, and yet distinct from other EBLV-1 strains circulating in the serotine bats ( 41 ). In addition, recent studies have demonstrated the geographical expansion of EBLV-1 in E. serotinus and E. isabellinus across Iberian Peninsula from Europe ( 12 ). In 2011, a new lyssavirus was confirmed in a M. schreibersii in the City of Lleida (north-eastern Spain), analysed as part of the rabies surveillance programme in Spain ( 42 ).…”
Section: Historical Overview Of Rabies In Europementioning
confidence: 99%
“…Otra serie de estudios del CNM se han centrado en la filogeografía del EBLV-1 a nivel europeo e ibérico Mingo, 2018). Existen dos subtipos de EBLV-1, el 1a, muy homogéneo y ampliamente distribuido de este a oeste desde Holanda hasta Rusia y Ucrania, con un subclado disyunto en el sur de Francia y el 1b, exclusivo de Holanda, extremo sur de Alemania y especialmente Francia, donde presenta varios subclados geográficos (Troupin, 2017;Mingo, 2018). En nuestros trabajos hemos encontrado que las cepas ibéricas forman un clado independiente dentro del subtipo 1b con cierta aparente estructura geográfica interna.…”
Section: Investigación Sobre Rabia En El Centro Nacional De Microbiologíaunclassified